Unravelling the connection between COVID-19 and Alzheimer’s disease: a comprehensive review - Shajahan, Shah Rezlan; Kumar, Suresh; Ramli, Muhammad Danial Che (Frontiers in Aging Neuroscience, 2024)
Currently, there exists a limited comprehension regarding the correlation between COVID-19 and Alzheimer’s disease (AD). To elucidate the interrelationship and its impact on outcomes, a comprehensive investigation was carried out utilising time-unrestricted searches of reputable databases such as Scopus, PubMed, Web of Science, and Google Scholar. Our objective was to evaluate the impact of various medical conditions on severe COVID-19-related events. We focused on identifying and analysing articles that discussed the clinical characteristics of COVID-19 patients, particularly those pertaining to severe events such as ICU admission, mechanical ventilation, pneumonia, mortality and acute respiratory distress syndrome (ARDS) a serious lung condition that causes low blood oxygen. Through careful data analysis and information gathering, we tried to figure out how likely it was that people with conditions, like AD, would have serious events. Our research investigated potential mechanisms that link AD and COVID-19. The ability of the virus to directly invade the central nervous system and the role of ACE-2 receptors were investigated. Furthermore, the OAS1 gene served as the genetic link between AD and COVID-19. In the context of COVID-19, our findings suggest that individuals with AD may be more susceptible to experiencing severe outcomes. Consequently, it is crucial to provide personalised care and management for this demographic. Further investigation is required to attain a comprehensive comprehension of the intricate correlation between Alzheimer’s disease and COVID-19, as well as its ramifications for patient outcomes.